Liver changes associated with canine monocytic ehrlichiosis in a dog: Case report (Research, Society and Development, 2025)
Hepatic alterations are characterized by a significant loss of liver function and may be triggered by various etiologies. Among them, canine ehrlichiosis, an infectious disease transmitted by ticks, stands out as a potential secondary cause, especially in endemic regions. This study aims to report a case of hepatic insufficiency in a mixed-breed female dog (SRD), secondary to Ehrlichia canis infection, which progressed with ascites. The patient presented with nonspecific clinical signs such as apathy, anorexia, vomiting, and abdominal distension. Diagnosis was established through laboratory tests, abdominal ultrasonography, and a positive test for E. canis. Treatment included antibiotic therapy, hepatic support, and ascites management. This report highlights the importance of early diagnosis of ehrlichiosis and its potential to cause severe liver damage, requiring a systematic and interdisciplinary clinical approach.